Clinical and epidemiological aspect of malignant neoplasm of conjunctiva in the Chelyabinsk region - L. E. Semenova; I. E. Panova; P. I. Musaeva (Российский офтальмологический журнал)
Malignant neoplasms of conjunctiva (MNC) are characterized by high degree of malignancy and predisposed to invasive growth and generalization of the process, which leads to fatal outcomes. Purpose: to investigate clinical and epidemiological aspects of malignant conjunctival tumors over a 18-year period starting in 2001. Material and methods. We analyzed the epidemiological factors of MNC in 51 patients aged 15 to 97 (average 63.1 ± 17.3), who were treated in the Center of Oncological ophthalmology at the Chelyabinsk regional clinical center of oncology and nuclear medicine. Results. The structure and morbidity changes of MNC are presented, showing the age and gender distribution of patients and revealing the clinical picture for varying types of the pathology. Long-term results were as follows: MNC relapses occurred in 11 patients (22.4 %) 36.0 ± 24.5 months after treatment. Tumor metastases into regional lymph nodes and hematogenous metastases averagely developed after 18.5 ± 6.8 years. Between 2008 and 2015, 9 patients (17.6 %) died. The Cancer Register of the Center was used to calculate the parameters of corrected cumulative survival rate for Chelyabinsk region population after MNC as a whole, as well as separately for melanomas and squamous cell carcinomas of the conjunctiva, and for the stages of the disease. The three-year survival rate for MNC was 80.5 %, for conjunctival melanoma 90.1 %, for squamous cell carcinomas 80.5 %. The 5-year survival rates were, respectively, 71.5, 80.1 and 60.5 %. The 3-year MNC survival rate for stages I and II of MNC was 100 %. For stage III, it was 76.9 %, and for stage IV, 33.3 %. The 5-year survival rates for stages I to IV of MNC were respectively, 100, 88.9, 69.2 % and 33.3 %. Conclusion. The new Center for oncological ophthalmology established within a multidisciplinary oncological treatment and prophylactic institution improved medical assistance and diagnostics of patients with MNP. The results obtained should be taken into account when developing preventive measures for the early detection of conjunctival malignancy.